2021
DOI: 10.1007/s11357-021-00359-5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal course of GDF15 levels before acute hospitalization and death in the general population

Abstract: Growth differentiation 15 (GDF15) is a potential novel biomarker of biological aging. To separate the effects of chronological age and birth cohort from biological age, longitudinal studies investigating the associations of GDF15 levels with adverse health outcomes are needed. We investigated changes in GDF15 levels over 10 years in an age-stratified sample of the general population and their relation to the risk of acute hospitalization and death. Serum levels of GDF15 were measured three times in 5-year inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
(88 reference statements)
1
1
0
Order By: Relevance
“…Similarly, HSP70 expression was elevated in smokers who experienced plaque erosion. Consistent with the published demographic differences between patients who experience plaque rupture and erosion, the patients in the plaque erosion group were significantly younger than those in the rupture group (51.1 ± 8.1 vs 59.7 ± 10.9), and we cannot exclude that the differences we observed in GDF15 and HSP70 levels are related to age; however, circulating GDF15 concentrations increases with age 68 suggesting that the observed increase in GDF15 with erosion is likely robust. Lastly, we demonstrated that OSGIN1 and OSGIN2 were up-regulated in the aortas of mice exposed to cigarette smoke.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, HSP70 expression was elevated in smokers who experienced plaque erosion. Consistent with the published demographic differences between patients who experience plaque rupture and erosion, the patients in the plaque erosion group were significantly younger than those in the rupture group (51.1 ± 8.1 vs 59.7 ± 10.9), and we cannot exclude that the differences we observed in GDF15 and HSP70 levels are related to age; however, circulating GDF15 concentrations increases with age 68 suggesting that the observed increase in GDF15 with erosion is likely robust. Lastly, we demonstrated that OSGIN1 and OSGIN2 were up-regulated in the aortas of mice exposed to cigarette smoke.…”
Section: Discussionsupporting
confidence: 83%
“…However, there was no correlation between GDF-15 and the SMI for females. GDF-15 levels were higher in females than in males in their 30 s; however, they were higher in males than in females when they were in their 50s 25 . The population observed during our study was in their 30 s, when this change begins to occur, which may be why there was no significant difference in females.…”
Section: Discussionmentioning
confidence: 69%